Therapeutic effects of beard lichen, Usnea barbata extract against Lactococcus garvieae infection in rainbow trout (Oncorhynchus mykiss). Issue 87 (April 2019) - Bilen, Soner; Sirtiyah, Abdulwahid Mohammed Almahdi; Terzi, Ertugrul
Abstract: In this study, therapeutic effects of aqueous methanolic extracts of beard lichen ( Usnea barbata ) against Lactococcus garvieae (ATCC 43921) in rainbow trout ( Onchorhynchus mykiss ) were investigated. Six different experimental groups [0 mg/100 μL (Control), 4 mg/100 μL, 8 mg/100 μL, 12 mg/100 μL, 6 mg/100 μL florfenicol (positive control), 6 mg/100 μL erythromycin (positive control)] were set up to determine effects of lichen extract on immune responses and survival rate. In the study, superoxide radical production was increased in fish treated with 12 mg beard lichen extract, florfenicol and erythromycin compared to that of control (P < 0.05). Lysozyme activity was generally decreased (P < 0.05) or no differences were observed in all experimental groups compared to that of control (P > 0.05). Myeloperoxidase was significantly increased in all antibiotic treated groups. No differences were observed in liver histology of experimental groups compared to control. Cytokine gene expressions were elevated in all experimental groups compared to that of control (P < 0.05), except IL-1β expression at 10th day sampling time. Other immune related genes (IL-8, TGF- β, IL-12 Beta, TNFα1, IL-10, COX-2, IL-6, TLR5, C3, IGM, MHC-II, iNOS, IgT, IFN1, IFN2, IFN reg) were also elevated in all experimental groups compared to that of control group. The survival rates obtained in 4 mg beard lichen treated group, 8 mg beard lichen treated group and erythromycin treated group were 73.08, 65.38 and 80.77% respectively. Our results suggest that beard lichen methanolic extract could be an effective therapeutic agent to be used against L. garvieae infection in rainbow trout at the dose of 4 mg/17.41 ± 0.3 g body weight/day. Highlights: We tested therapeutical effects of Usnea barbata in O. mykiss against L. garvieae. U. barbata provides a new cure in O. mykiss at the dose of 4 mg/17.41 ± 0.3 g body weight/day against L. garvieae . U. barbata extract could be used as a therapeutic in O. mykiss .